If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-(x+3)/2=-x-1
We move all terms to the left:
4-(x+3)/2-(-x-1)=0
We add all the numbers together, and all the variables
-(x+3)/2-(-1x-1)+4=0
We get rid of parentheses
-(x+3)/2+1x+1+4=0
We multiply all the terms by the denominator
-(x+3)+1x*2+1*2+4*2=0
We add all the numbers together, and all the variables
-(x+3)+1x*2+10=0
Wy multiply elements
-(x+3)+2x+10=0
We get rid of parentheses
-x+2x-3+10=0
We add all the numbers together, and all the variables
x+7=0
We move all terms containing x to the left, all other terms to the right
x=-7
| 5-8x+4x^2=0 | | 2x+2=5x-9 | | 9x+22=49 | | 3(x+1)=x+41 | | 3(2x-9)=4x-13 | | 7(x+5)=2(2x+25) | | p=(9)/(7)p+28 | | 4×2^2x-2-5×2^x-1+1=0 | | 12=1h-1h-1h-1h-1h-1h-1h-1h | | 15x+29(x-2)=249 | | {4×+5y=1 | | P(n,4)=32760 | | 5(x+3)+2(x-4)=2 | | 3=1.09^n | | v^2-242=0 | | 22=16+3×b | | 2/3x^2+1/6x+3=0 | | 4.9t^2+100t-392=0 | | 96-c=20-12c | | 8x-5=2-19 | | 3x/13+5/13=2x/13=-4/13 | | 3x+5=2x=-4 | | (-2)x+4^3=68 | | 8x+(-15)=17 | | (-34)-7x=(-69) | | 5(x+2)=3(2x-7) | | x/3+(-4)(3)=(-9) | | 9=5x+25/5 | | 3(n+2)+2-4n=-2 | | x-3/4+2x-5/3=11 | | 29+(x)/(-7)=27 | | 3/5x+5/3x=5/3+3/5x |